The provision of facilities and services for the neighbourhood : A case study of neighbourhood areas in Manjung Perak / Norainah Abdul Rahman - Abdul Rahman, Norainah (Institute of Graduate Studies, 2017)
Neighbourhood is a place where the community is attached with the land use and amenities. The facilities and services are important aspect to the residents in their neighbourhood. The neighbourhood facilities and services are based on the planning guidelines were adopted by local governments. The issue that is often being questioned is the provision that can meet the residents’ requirements and needs. The aim of this study is to establish facilities and services evaluation approach. The study has developed a satisfaction model incorporated with physical and social factors to establish the evaluation approach. Empirical research has shown the importance of residents’ evaluating their neighbourhood. The physical factors are adequacy, amenity condition, distance, accessibility and maintenance. The social factors are feeling convenient, feeling safe and feeling comfort. The research design employed the quantitative approach with qualitative data. The quantitative approach was used to collect primary data from the residents through a questionnaire survey. The qualitative data was used to collect both primary and secondary data. The primary data is from the open-ended questions in the questionnaire survey and the site inventory survey. The secondary data is from the local government and agencies related. Three selected neighbourhoods in Manjung Perak Malaysia are in Seri Manjung, Sitiawan and Lumut. The evaluation was to measure the level of satisfaction among the residents on the existing facilities and services in their neighbourhood. The guidelines used by the local government were also appraised to compare the compliance of facilities and services provided with the planning guidelines. There are three key findings of the research...